Pengaruh Pupuk Organik Eceng Gondok dan Pupuk Hayati Terhadap Sifat Biologi Tanah, Pertumbuhan, dan Hasil Tanaman Sawi (Brassica Juncea L.) - PATRA, MAEZA; KARTINI, NI LUH; SONIARI, NI NENGAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Effect of Hyacinth Organic Fertilizer and Biofertilizer on Biological Properties of Soil, Growth and Yield of Sawi Plants (Brassica juncea L.) This study aims to determine the effect of interactions between water hyacinth organic fertilizer and biofertilizer on the biological properties of soil, growth and yield of mustard greens. This research was conducted in April 2018 until June 2018 at Banjar Taman Tanda, Baturiti Village, Baturiti District, Tabanan Regency. The experiment used a randomized block design (RBD) with 2 factor, namely Eceng Gondok organic fertilizer 3 levels (P0, P1, P2), and biological fertilizer 3 levels (M0, M1, M2). 9 combination treatments and 3 replications so that there were 27 trial tests and data analysis using the Costat program and continued with the BNT test at 5% if the treatment was significantly. Parameters observed were pH, total N, organic C, microorganism population, plant height, fresh weight and dry weight of plants. the best treatment of water hyacinth organic fertilizer and biofertilizer on the yield of mustard plants was shown by a combination of 80 tons ha-1 of water hyacinth organic fertilizer and 60 ml of biological fertilizer (1% concentration solution) of 6,940 tons ha-1 and increased 24 % of control. This treatment provides the best response to green mustard plants.